2015
DOI: 10.3329/bjp.v10i3.23079
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense weekly paclitaxel and carboplatin compared with conventional paclitaxel and carboplatin treatment for stage II-IV ovarian cancer patients

Abstract: <p>We investigated dose-dense weekly paclitaxel and carboplatin compared with conventional paclitaxel and carboplatin treatment on stage II-IV ovarian cancer patients. Between July, 2011, and October, 2014, a total of 221 patients was randomly assigned to receive dose-dense weekly paclitaxel and carboplatin group (n = 109) and conventional paclitaxel and carboplatin group (n = 112), just after the sixth chemotherapy cycles, and at 12 months after randomization. Median progression-free survival (PFS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Histopathological analysis of the patients in the study found that patients with mesenchymal transition (MT) type receiving dose-dense regimen had a significantly better median PFS (1.8 vs 1.2 years, p = 0.01) [ 15 ]. Three other experiments also showed that dose-dense treatment improved survival time compared with conventional three-weekly treatment [ 16 – 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Histopathological analysis of the patients in the study found that patients with mesenchymal transition (MT) type receiving dose-dense regimen had a significantly better median PFS (1.8 vs 1.2 years, p = 0.01) [ 15 ]. Three other experiments also showed that dose-dense treatment improved survival time compared with conventional three-weekly treatment [ 16 – 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of ICON8 trial had been published 26 27. Another study conducted reported that dose-dense weekly paclitaxel and carboplatin treatment improves survival compared with conventional paclitaxel and carboplatin treatment 28. Therefore, it seems that an updated comprehensive meta-analysis is required to shed light on the effectiveness and safety of weekly paclitaxel with carboplatin regimen compared with 3-weekly paclitaxel with carboplatin regimen for women with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%